Computational design of mechanical metamaterials - Bonfanti, Silvia; Hiemer, Stefan; Zulkarnain, Raja; Guerra, Roberto; Zaiser, Michael; Zapperi, Stefano (Nature Computational Science, 2024)
In the past few years, design of mechanical metamaterials has been empowered by computational tools that have allowed the community to overcome limitations of human intuition. By leveraging efficient optimization algorithms and computational physics models, it is now possible to explore vast design spaces, achieving new material functionalities with unprecedented performance. Here, we present our viewpoint on the state of the art of computational metamaterials design, discussing recent advances in topology optimization and machine learning design with respect to challenges in additive manufacturing.
CRIS-Team Scopus Importer:2024-09-06